Static Analysis : 22nd International Symposium, SAS 2015, Saint-Malo, France, September 9-11, 2015, Proceedings - Blazy, Sandrine; Jensen, Thomas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 22nd International Static Analysis Symposium, SAS 2015, held in Saint-Malo, France, in September 2015. The 18 papers presented in this volume were carefully reviewed and selected from 44 submissions. All fields of static analysis as a fundamental tool for program verification, bug detection, compiler optimization, program understanding, and software maintenance are addressed, featuring theoretical, practical, and application advances in the area.
Keywords: Logic design; Software engineering; Computer science; Logics and Meanings of Programs; Software Engineering; Programming Languages, Compilers, Interpreters; Mathematical Logic and Formal Languages